Description of two new species of Hisonotus Eigenmann & Eigenmann, 1889 (Ostariophysi, Loricariidae) from the rio Parana-Paraguay basin, Brazil - Roxo, Fabio F. [UNESP] (2014)
Two new species of Hisonotus are described from the rio Parana-Paraguay basin in Brazil. The most remarkable features of the new species are the odontodes forming longitudinally aligned rows (one odontode after the other, but not necessarily forming parallel series) on the head and trunk (vs. odontodes not forming longitudinally aligned rows), a pair of rostral plates at the tip of the snout (vs. a single rostral plate), the functional v-shaped spinelet (vs. spinelet non-functional, square-shaped, or absent). These features suggest close phylogenetic relationships with Hisonotus bockmanni, H. insperatus, H. luteofrenatus and H. piracanjuba. Additionally, both new species are distinguished from their congeners by characters related to head length and depth, orbital diameter, suborbital depth, caudal peduncle depth, pectoral-fin spine length, snout length and counts of teeth. Hisonotus paresi sp. n. further differs from its congeners by having contrasting dark geometric spots on the anterodorsal region of the body, a character lacking in H. oliveirai sp. n. The variation in number and shape of the rostral plate, posterior rostrum plates, infraorbitals and the preopercle in both new species and in H. insperatus are discussed.